The identity issue in the journey of Présence Africaine - (:unkn) unknown (My University, 2022)
This article examines the identity issue as expressed in the historical journey of the intellectual movement Présence Africaine. It highlights a fundamental dimension of the commitment of that movement not yet explored in academic research. The current study which rediscovers the challenges and the great events, which shaped the reputation of Présence Africaine as an African intellectual movement with a journal and a publishing house, also deals with the identity issue through philosophical and theological debates as well as in reference to the independence era in Africa. The relevance of such a study is due to the topicality of the identity issue for contemporary societies.
Keywords: African Research